A syntactic-semantic optimality theoretic model on Hakka topic-comment construction - Yu-Ching Tseng (Universitas Syiah Kuala, 2021)
The purpose of this paper is to show how the basic Topic-Comment ordering pattern of the Hakka can be accounted for by the constraint-based optimality theory. Part of the linguistic data used in this paper is adopted from Xu (2002), while those examples presented to show syntactic tests are created by the author. These sentences have been further checked and confirmed by a native speaker of Hakka. This paper proposes an Optimality Theoretic (OT) model that takes into account both syntactic and semantic considerations. It shows that semantic information comes into play successively at different points of OT grammar. First, integrating semantic information into the schema of OT syntax works precisely to describe the Hakka topic-initial sentence pattern. The alignment constraints incorporate information about the semantically defined topic and comment constructions into the constraint design, which interacts with other markedness constraints to filter linguistic constructions during production. Second, semantic constraints are formed to further evaluate form-meaning pairs during the process of interpretation. In this aspect, semantic notions including contrastiveness and markedness are incorporated into the theoretical plan with the purpose of pairing syntactically well-formed sentences with appropriate meaning. The paper successfully presents an optimization model illustrating how syntax and semantics cooperate to pair meanings with linguistic constructions in forming linguistic expressions.